Circulating CD15+LOX‐1+ PMN‐MDSCs are a potential biomarker for the early diagnosis of non‐small‐cell lung cancer. Issue 8 (17th May 2021) - Tian, Xinyu; Wang, Ting; Zheng, Qisi; Tao, Yue; Dai, Lei; Shen, Han
Abstract: Aims: Non‐small‐cell lung cancer (NSCLC) is the most common clinical lung cancer. Polymorphonuclear‐myeloid derived suppressor cells (PMN‐MDSCs), which are the major population of MDSCs, are involved in NSCLC progression. Recently, it was found that lectin‐type oxidized LDL receptor 1 (LOX‐1) could identify human PMN‐MDSCs. However, the role of CD15 + LOX‐1 + PMN‐MDSCs in NSCLC early diagnosis has not been revealed. Here, we tried to confirm the application of the newly identified CD15 + LOX‐1 + PMN‐MDSCs in the early diagnosis of NSCLC. Methods: Flow cytometry (FCM) was used to detect the proportion of CD15 + LOX‐1 + PMN‐MDSCs in the peripheral blood (PB) of healthy controls (HC) and NSCLC patients. The correlation of CD15 + LOX‐1 + PMN‐MDSC frequency with levels of cytokeratin 19‐fragments (CYFRA21‐1), carcinoembryonic antigen (CEA), and carbohydrate antigen 125 (CA125) was analysed. Receiver operating characteristic (ROC) curve was used to estimate the diagnostic efficacy of CD15 + LOX‐1 + PMN‐MDSCs for NSCLC. Additionally, the association of CD15 + LOX‐1 + PMN‐MDSC frequency with NSCLC prognosis/recurrence after surgery was explored. Results: The proportion of CD15 + LOX‐1 + PMN‐MDSCs increased in PB of NSCLC patients. CD15 + LOX‐1 + PMN‐MDSC proportion was positively correlated with levels of CEA, CA125 and CYFRA21‐1. Detection of PMN‐MDSC percentage in PB owed high sensitivity and specificity for NSCLC diagnosis. The proportion of CD15 + LOX‐1 + PMN‐MDSCs decreased in patients after surgery. The frequency of CD15 + LOX‐1 + PMN‐MDSCs was lower in NSCLC patients without recurrence compared to those with recurrence after surgery. Conclusions: Circulating CD15 + LOX‐1 + PMN‐MDSCs are a potential diagnostic marker for NSCLC, and are associated with NSCLC prognosis and recurrence after surgery.